Temperature dependent amplified spontaneous emission of vacuum annealed perovskite films. Issue 26 (10th March 2017) - Qin, Liang; Lv, Longfeng; Li, Chunhai; Zhu, Lijie; Cui, Qiuhong; Hu, Yufeng; Lou, Zhidong; Teng, Feng; Hou, Yanbing
Abstract : The vacuum annealed perovskite film exhibits a smooth morphology and good crystallinity, which could enhance the temperature dependent ASE performance. Abstract : Hybrid organic–inorganic halide perovskite crystals exhibit potential applications in amplified spontaneous emission (ASE) devices. The enhancement of the photoluminescence (PL) and full width at half maximum (FWHM) with the temperature dependent phase transition are beneficial to investigate the low threshold of ASE devices. However, the ASE performance and temperature dependent transition characteristics of perovskite films critically depend on morphology and crystallinity. In this paper, we propose vacuum-assisted thermal treatment to effectively prepare smooth, condense and well-crystalline MAPbI3 perovskite films. An obvious temperature dependent phase transition occurs in the vacuum annealed MAPbI3 perovskite films, leading to an increase in PL intensity, which could non-monotonically lower the threshold for ASE. Investigating the transient performance at the temperature dependent phase transition underlines an important step in optimizing these novel materials.